Hurricane Matthew in 2100: effects of extreme sea level rise scenarios on a highly valued coastal area (Palm Beach, FL, USA) - Boyden, Patrick; Casella, Elisa; Daly, Christopher; Rovere, Alessio; MARUM - Center for Marine Environmental Sciences, University of Bremen, Bremen, Germany; ZMT - Leibniz Center for Tropical Marine Research, Bremen, Germany; Leiden University College, Leiden, The Netherlands (Geo-Marine Letters, 2021)
Sea-level rise represents a severe hazard for populations living within low-elevation coastal zones and is already largely affecting coastal communities worldwide. As sea level continues to rise following unabated greenhouse gas emissions, the exposure of coastal communities to inundation and erosion will increase exponentially. These impacts will be further magnified under extreme storm conditions. In this paper, we focus on one of the most valuable coastal real estate markets globally (Palm Beach, FL). We use XBeach, an open-source hydro and morphodynamic model, to assess the impact of a major tropical cyclone (Hurricane Matthew, 2016) under three different sea-level scenarios. The first scenario (modern sea level) serves as a baseline against which other model runs are evaluated. The other two runs use different 2100 sea-level projections, localized to the study site: (i) IPCC RCP 8.5 (0.83 m by 2100) and (ii) same as (i), but including enhanced Antarctic ice loss (1.62 m by 2100). Our results show that the effective doubling of future sea level under heightened Antarctic ice loss amplifies flow velocity and wave height, leading to a 46% increase in eroded beach volume and the overtopping of coastal protection structures. This further exacerbates the vulnerability of coastal properties on the island, leading to significant increases in parcel inundation. Universität Bremen (1013) https://github.com/pboyden/Palm_Beach_XBeach